ROBOT APUNG PEMBERI PAKAN IKAN KOLAM AIR TAWAR BERBASIS ARDUINO - Muhammad Sadam; Tan Suryani Sollu; Rizana Fauzi (Foristek, 2021)
The need for fish is increasing every year. Because it is increasing every year, fish farming must be increased in line with the use of improved fish farming technology. So that it requires an adequate technological structure and mechanization. Based on this background, the arduino-based floating robot for feeding freshwater pond fish is designed to be able to apply technology that is useful in feeding farmed fish. The arduino based floating robot fish feeding freshwater fish pond using Arduino Mega 2560 as its microcontroller, 4 Sharp 2Y0A21 sensors that function to detect pond walls, RTC functions as a timer so that it can feed fish according to the time set on the tool, LCD functions as the information viewer of the tool, the L298N motor driver controls the DC motor and the servo motor functions as the opening or closing of the food valve on the appliance. In the test, the arduino based floating robot fish feeding freshwater fish pond is able to float in water and can feed fish based on the time available on the tool. The Sharp 2Y0A21 sensor as a pool wall detector has a distance reading in the range of 1 millimeter to 10 centimeter. The robot can avoid the pool wall with a span of 3 - 7 seconds, this is influenced, among others, by surging water, wind, sensor response, and DC motors.